Profit sharing under the threat of nationalization - Luca Di Corato (Fondazione Eni Enrico Mattei (FEEM), 2010)
A government bargains a mutually convenient agreement with a multinational corporation to extract a natural resource. The corporation bears the initial investment and earns as a return a share on the profits. The host country provides access and guarantee conditions of operation. Being the investment totally sunk, the corporation must account in its plan not only for uncertainty on market conditions but also for the threat of nationalization. In a real options framework where the government holds an American call option on nationalization we show under which conditions a Nash bargaining is feasible and leads to attain a cooperative agreement maximizing the joint venture surplus. We find that the threat of nationalization does not affect the investment time trigger but only the feasible bargaining set. Finally, we show that the optimal sharing rule results from the way the two parties may differently trade off rents with option value.
Keywords: C7; D8; K3; F2; O1; 330; Real Options; Nash Bargaining; Expropriation; Natural Resources; Foreign Direct Investment; Rohstoffressourcen; Rohstoffwirtschaft; Direktinvestition; Bergrecht; Bergbaupolitik; Verstaatlichung; Investitionsrisiko; Nash-Gleichgewicht